RDUR, a lncRNA, Promotes Innate Antiviral Responses and Provides Feedback Control of NF-κB Activation - Chen, Yuhai; Hu, Jiayue; Liu, Shasha; Chen, Biao; Xiao, Meng; Li, Yingying; Liao, Yuan; Rai, Kul Raj; Zhao, Zhonghui; Ouyang, Jing; Pan, Qidong; Zhang, Lianfeng; et al. (Frontiers in Immunology, 2021)
Influenza A virus (IAV), a highly infectious respiratory pathogen, remains a major threat to global public health. Numerous long non-coding RNAs (lncRNAs) have been shown to be implicated in various cellular processes. Here, we identified a new lncRNA termed RIG-I-dependent IAV-upregulated noncoding RNA (RDUR), which was induced by infections with IAV and several other viruses. Both in vitro and in vivo studies revealed that robust expression of host RDUR induced by IAV was dependent on the RIG-I/NF-κB pathway. Overexpression of RDUR suppressed IAV replication and downregulation of RDUR promoted the virus replication. Deficiency of mouse RDUR increased virus production in lungs, body weight loss, acute organ damage and consequently reduced survival rates of mice, in response to IAV infection. RDUR impaired the viral replication by upregulating the expression of several vital antiviral molecules including interferons (IFNs) and interferon-stimulated genes (ISGs). Further study showed that RDUR interacted with ILF2 and ILF3 that were required for the efficient expression of some ISGs such as IFITM3 and MX1. On the other hand, we found that while NF-κB positively regulated the expression of RDUR, increased expression of RDUR, in turn, inactivated NF-κB through a negative feedback mechanism to suppress excessive inflammatory response to viral infection. Together, the results demonstrate that RDUR is an important lncRNA acting as a critical regulator of innate immunity against the viral infection.